Odpowiedzi

2009-10-14T19:51:37+02:00
A) (a+b)²=x2+6x+9
(a-b)²=x2-6x+9
(a+b)(a-b)=a2-b2=x2-9
(a+b)³=x3+9x2+27x+27
(a-b)³=x3-9x2+27x+27
(a+b)(a2-ab+b2)=a3+b3=x3+27
(a-b)*(a²+ab+b²)=a3-b3=x3-27

b)(a+b)²= 9x2+12x+4
(a-b)²=9x2-12x+4
(a+b)(a-b)=a2-b2=9x2-4
(a+b)³=27x3+54x2+36x+8
(a-b)³=27x3-54x2+36x+8
(a+b)(a2-ab+b2)=a3+b3=27x3+8
(a-b)*(a²+ab+b²)=a3-b3=27x3-8

c)(a+b)²=4+4x+x2
(a-b)²=4-4x+x2
(a+b)(a-b)=a2-b2=4-x2
(a+b)³=8+12x+6x2+x3
(a-b)³=8-12x+6x2+x3
(a+b)(a2-ab+b2)=a3+b3=8+x3
(a-b)*(a²+ab+b²)=a3-b3=8-x3

d)(a+b)²=16x2+16x+4
(a-b)²=16x2-16x+4
(a+b)(a-b)=a2-b2=16x2-4
(a+b)³=64x3+96x2+48x+8
(a-b)³=64x3-96x2+48x+8
(a+b)(a2-ab+b2)=a3+b3=64x3+8
(a-b)*(a²+ab+b²)=a3-b3=64x3-8

f)(a+b)²=2+2√2+1=3+2√2
(a-b)²=2-2√2+1=3-2√2
(a+b)(a-b)=a2-b2=2-1=1
(a+b)³=2√2+6+3√2+1=7+5√2
(a-b)³=2√2-6+3√2+1=5√2-5
(a+b)(a2-ab+b2)=a3+b3=2√2+1
(a-b)*(a²+ab+b²)=a3-b3=2√2-1